Control of the chemiluminescence spectrum with porous Bragg mirrors. (May 2015) - Varo, Simone; Criante, Luigino; Passoni, Luca; Dalle Vedove, Andrea; Aluicio-Sarduy, Eduardo; Di Fonzo, Fabio; Lanzani, Guglielmo; Scotognella, Francesco
Abstract : Tunable, battery free light emission is demonstrated in a solid state device that is compatible with lab on a chip technology and easily fabricated via solution processing techniques. A porous one dimensional (1D) photonic crystal (also called Bragg stack or mirror) is infiltrated by chemiluminescence (CL) rubrene-based reagents. The Bragg mirror has been designed to have the photonic band gap overlapping with the emission spectrum of rubrene. The CL reaction occurs in the pores of the photonic crystal and the emission spectrum of the dye is modulated according to the photonic band gap position. This is a compact, powerless emitting source that can be exploited in disposable photonic chips for sensing and point of care applications.